1967
DOI: 10.1149/1.2426482
|View full text |Cite
|
Sign up to set email alerts
|

Impurity Redistribution in a Semiconductor during Thermal Oxidation

Abstract: A general review of mathematical treatments on this redistribution phenomena has been made and discussed. A series method is developed and exact solutions describing the redistributed impurity concentration profiles in both the oxide and the semiconductor can be given. Boundary conditions of diffusion equations are discussed according to different physical situations. Special cases are treated for three initial impurity concentration profiles in silicon: Gaussian, complementary error function, and uniform. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
1984
1984

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The ion microprobe has been used in this study to determine the boron concentration on both sides of the interface thus providing a direct measure of the segregation coefficient. This avoids dependence on a modeling procedure as required by the above studies (2)(3)(4)(5)(6)(7)(8). Such a technique has been emplo~-ed (10,11) 4x previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ion microprobe has been used in this study to determine the boron concentration on both sides of the interface thus providing a direct measure of the segregation coefficient. This avoids dependence on a modeling procedure as required by the above studies (2)(3)(4)(5)(6)(7)(8). Such a technique has been emplo~-ed (10,11) 4x previously.…”
Section: Discussionmentioning
confidence: 99%
“…However, this phenomenon was never completely understood and further experimentation showed that very small amounts of H2 in the diffusion ambient drastically reduce the masking ability of Mo films against its diffusion. The importance of the enhanced diffusion of B in SiO2 when heated in H2 and H20 ambients (2) has had important consequences for B-doped polysilicon-gate MOSFET's and has been described by others (3)(4)(5)(6). Heat-treatment of St-gate MOSFET's in H2 and H20 ambients has been observed to decrease the p-channel enhancement mode MOSFET threshold or produce p-channel depletion mode devices instead of the desired enhancement mode device.…”
Section: Publication Costs O] This Article Were Partially Assisted By...mentioning
confidence: 99%